THE ROLE OF LEADRERSHIP, DISCIPLINE AND THE EMPLOYEES’ PERFORMANCE OF MINISTRY OF RELIGION KEPAHIANG REGENCY - Slamet Widodo; F Romsi; Trisna Murni (UNIB Press, 2020)
The purpose of the study to determine the role of leadership to be one of the key factors in the life of the organization. leadership, discipline, quality must be owned by the leader's office, is fundamentally individual advantages, including the ability to direct subordinates skills, provide motivation and at the same time is able to provide strict sanctions, with the employee if the employment irregularities. In addition it must be able to personally leader in conflict management and wise in making decisions. Performance in the Office of Religious Affairs Kepahiang District. who has not run well, so the decline in the quality of performance. The method used is the method of qualitative description. with the hope to expose all of the facts and events, with the hope of obtaining accurate research results and not merely engineering. For data collection using several ways including: interviews and questionnaires. The research results are leadership role as a blocker disorder is head office has memperedeksi all possibilities that will arise. As is also the head office divider human resources, as negotiators head office always negotiating with internal and external parties, local government. usual. The head office influence subordinates well enough, be friendly and do not distinguish one another, addressing example, and a good personality, well-dressed, saying gently, not favoritism. The head office can also give effect to encourage and give encouragement, confidence, a good example. Motivate subordinates, provide encouragement and inspiration. appreciation / compliments. The head can also create a conducive atmosphere in the work, giving a sense of responsibility, family, clean environment, giving pasilitas work, provide direction and guidance. Instilling the value of discipline. Creative office of the ministry of religion is not going well, had a good example, the price of mutual respect . Remuneration/incentive goes well, the awards also performed in groups. Communication was excellent. Good enough responsibility, commitment to a given task, cooperation, communication with colleagues.